Information Technology, Marketing Database and the Process of Integrated Marketing Communications (IMC): A Resource-Capability Nexus - Ahmad, Ayaz; Salleh, Salniza Md.; Perumal, Selvan a/l (Pakistan Journal of Humanities and Social Sciences, 2018)
This study aims at identifying and conceptually linking Information Technology, Marketing Database and the IMC process in a resource paradigm. It also conceptually posits the mediated role of Marketing Database to further transmit the absorbed effect to the IMC process. Review of the past studies has been done to conceptually connect these resources and/or capabilities. This paper establishes different relationships to be further tested empirically for both the academia and industry professionals. The main contribution is to conceptually theorize all the three concept and linking them conceivably that were either missing or vague in the marketing communication literature. Further, it also provides a research avenue to seek the complementarity of such resources by utilizing the extended RBV theory. The theoretical framework proposed is based on past literature from the RBV and marketing communications literature positing some new structural paths beside certain previous linkage (s) if any.